Teaching Methods in Pesantren to Tackle Religious Radicalism - Taufik Abdillah Syukur (Jurnal Pendidikan Islam, 2019)
Religious radicalism has been a problem and a burning issue in social religion life in Indonesia. Government and the society including educational institutions like pesantren need to collaborate to solve this problem. This study was aimed at investigating the teaching methods applied in pesantren as an effort to tackle religious radicalism. This research used descriptive qualitative method. Techniques used were observation, interview and documentation. Interview was done to several key informants from pesantren to gather relevant information. The results showed that pesantren around the capital city of Jakarta still applied learning methods namely sorogan, bandongan, Islamic classic book reading. Those methods were designed to promote discussion in learning Islamic material. In addition, the learning methods developed santri academic achievement nurture their social skills. Given these skills and competencies, santri were taught to respect opinions of others and promote the effort to tackle religious radicalism in pesantren.